Effect of FBG Fiber Dosimeter Division in Sensing Capability for Low Radiation Doses (Journal of the College of Basic Education, 2024)
رA fiber Bragg grating (FBG) as a dosimeter is developed in this simulation study (based on Optisystem 21 software) by dividing its region into five individual regions. The division includes the same properties for all regions, which is a standard SiO2 optical fiber material. In dosimeters, it is convenient to introduce dopants to increase the fiber sensitivity. The new design accepts dopants and can work without such a dopant. Measurements for sensing deflected signals from the FBG sensor confirmed increased sensitivity for low-rate radiation doses in comparison to one bulk region in a traditional fiber dosimeter. The sensitivity of this dosimeter is based on both the FWHM line shape function and the amplitude of the deflected signals. The FBG dosimeter sensor can respond to low-dose radiation in a noticeable manner according to the type of applied simulated effect. Dosimeter body division for multi-regions gives rise to sensitivity in comparison to the traditional bulk region. The measured FWHM from the line-shape function for overall observed signals fluctuates from 0.374 MHz under applied temperature, stress x, y, z, and strain to 0.358, 0.373, 0.3733, 0.368, and 0.3737 MHz, respectively. While this range follows different fitting functions: Sin, Exp.Decay, SinSqu., Exp.Decay3, and GaussAmpl. For last effects, according to measured effect. The same measurements were carried out for signal amplitude variation, with these effects giving a variety of relationships indicating their existing contribution. Results confirmed an efficient tool for use in sensing for low x-ray and gamma ray radiation dose applications versus traditional bulk FBG sensor type.